2015
DOI: 10.1103/physrevlett.115.186102
|View full text |Cite
|
Sign up to set email alerts
|

Phonons in Ultrathin Oxide Films: 2D to 3D Transition in FeO on Pt(111)

Abstract: The structural and magnetic properties of ultrathin FeO(111) films on Pt(111) with thicknesses from 1 to 16 monolayers (MLs) were studied using the nuclear inelastic scattering of synchrotron radiation. A distinct evolution of vibrational characteristics with thickness, revealed in the phonon density of states (PDOS), shows a textbook transition from 2D to 3D lattice dynamics. For the thinnest films of 1 and 2 ML, the low-energy part of the PDOS followed a linear ∝E dependence in energy that is characteristic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 58 publications
1
20
0
Order By: Relevance
“…The power n in the dependence of g ( ν ) ∝  v n at low frequencies is still the subject of debate mainly because the analysis performed on different assemblies of NPs suffer from the uncertainties on data corrections and heterogeneities of the samples. Very recently the 2D–3D transition has been clearly observed in ultrathin FeO films but it concerns nonmetallic systems containing also optical modes and whose acoustic modes are only confined in one direction50.…”
Section: Discussionmentioning
confidence: 99%
“…The power n in the dependence of g ( ν ) ∝  v n at low frequencies is still the subject of debate mainly because the analysis performed on different assemblies of NPs suffer from the uncertainties on data corrections and heterogeneities of the samples. Very recently the 2D–3D transition has been clearly observed in ultrathin FeO films but it concerns nonmetallic systems containing also optical modes and whose acoustic modes are only confined in one direction50.…”
Section: Discussionmentioning
confidence: 99%
“…To accurately treat the electron of transition metal oxides, the on-site column repulsion was described for FeO/Pt biphase systems by DFT+U approach [48][49] with U -J = 3 eV for Fe 3d orbitals, as used in previous studies. 11,35,50 To model the methanol partial oxidation on metal mono-phase, a four-layer p(3×3) Pt(111) slab ( Fig. S1) was used (9 Pt atoms in each layer) with 4 × 4 × 1 k-point sampling.…”
Section: Methodsmentioning
confidence: 99%
“…20,21 Previous lattice dynamics studies of surfaces, thin films, interfaces, and multilayers revealed drastic modifications of their phonon density of states (PDOS) with respect to the bulk counterparts with the main features being an enhancement of the number of phonon states at low and high energy and suppression and shift of the peaks. [22][23][24][25][26][27] In EuO, such phonon anomalies, combined with the strong interaction between spins and lattice vibrations could potentially increase the probability for undesired spin flips thus reducing the degree of spin polarization along certain crystallographic directions. This fact, combined with the ongoing efforts for epitaxial strain manipulation of the Curie temperature in thin EuO films 28,29 makes lattice dynamics and spin-phonon interaction investigations in strained EuO films exhibiting thicknesses and configurations similar to those envisaged for tunnel junction applications indispensable.…”
Section: Introductionmentioning
confidence: 99%